Best Answer

Just like there is a formula for solving quadratic equations, there is one for solving cubics, but it is much larger. Cubics three roots (or zeroes, or solutions). The formula is too large to be read comfortably here, so I've included a link to the relevant Wikipedia page where you can see the full formula; check under "related links".

More answers

First set the function equal to zero. x^3 - 4*x^2 - 9*x + 36 = 0 Then factorise the left hand side. x^2*(x-4) - 9*(x-4) = 0 (x-4)*(x^2-9) = 0 or (x-4)*(x-3)*(x+3) = 0 For the product [multiple] of these three factors to be zero, one of them must be zero. So, x-4 = 0 or x-3 = 0 or x+3 =o ie x = 4 or x = 3 or x = -3

Q: How do you get the zeros x3 4x2 9x plus 36?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x + 47 = 9x + 11 6x + 36 = 9x 36 = 3x 12 = x

44 = 9x +8 36=9x 4=x

9x+18y = 36 18y = -9x+36 y = -1/2x+2 which is now in slope intercept form the slope being -1/2

(5x+4)(9x+9) FOIL First (5x*9x=45x**2) Outside (5x*9=45x) Inside (4*9x=36x) Last (4*9=36) 45x**2+45x+36x+36 45x**2+81x+36 9(5x**2+9x+4x)

10x + 8x - 6x3 + 4x2 + 12x3 - x add the like terms. all the x's are like terms. al the x squared are like terms. all the x cubed are liked terms. 6x3 + 12x2 + 9x

Related questions

Dividend: x3+4x2-9x-36 Divisor: x+3 Quotient: x2+x-12

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "divided by", "equals".

The discriminant is 33.

6x + 47 = 9x + 11 6x + 36 = 9x 36 = 3x 12 = x

sure it does... that would be true

44 = 9x +8 36=9x 4=x

9x+18y = 36 18y = -9x+36 y = -1/2x+2 which is now in slope intercept form the slope being -1/2

(5x+4)(9x+9) FOIL First (5x*9x=45x**2) Outside (5x*9=45x) Inside (4*9x=36x) Last (4*9=36) 45x**2+45x+36x+36 45x**2+81x+36 9(5x**2+9x+4x)

10x + 8x - 6x3 + 4x2 + 12x3 - x add the like terms. all the x's are like terms. al the x squared are like terms. all the x cubed are liked terms. 6x3 + 12x2 + 9x

(x + 12)(x - 3)

x - 4. x^2 + 5x - 36 = (x - 4) (x + 9) x^2 - 9x + 20 = (x - 4) (x - 5)

11 + 9X